2016
DOI: 10.1016/j.nbd.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro prion-like behaviour of TDP-43 in ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is the most common form of motor neuron disease (MND), and > 95% of familial and sporadic cases involve the deposition of insoluble aggregated, phosphorylated and cleaved TDP-43 protein. Accumulating clinical and biological evidence now indicates that ALS bears a number of similarities to the prion diseases, with TDP-43 acting as a misfolded ‘prion-like’ protein demonstrating similar underlying pathobiology. Here we systematically address the hypothesis that ALS is a prion-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 69 publications
8
107
3
Order By: Relevance
“…In vitro, the intercellular transfer of TDP-43 has been demonstrated [21, 47, 57, 67]. However, whether this also occurs in vivo remains an open question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, the intercellular transfer of TDP-43 has been demonstrated [21, 47, 57, 67]. However, whether this also occurs in vivo remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…This was mediated by the packaging of TDP-43 into microvesicles or exosomes, which were more effective at transmission than free protein. Linking this phenomenon to clinical observations, when cell culture models were seeded with phosphorylated TDP-43 +ve insoluble fractions from ALS and FTLD patient brain or spinal cord, there was a significant increase in intracellular endogenous TDP-43 aggregation and subsequent cell death [44, 57]. To follow on from this we examined how motor neuron injury and subsequent degeneration mobilises TDP-43 in vivo and may contribute to pathogenicity in ALS.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption that cortical neurons (Betz cells) are the first to become involved followed by the α-motor neurons, tends to favor Charcot's theory [35], namely, that ALS originates in the lateral funiculus (i. e., corticospinal tract, where the axons of the Betz cells are located) and only then affects the α-motor neurons in the anterior horn of the spinal cord [36]. The sources of the very first malfunctions within the protein TDP-43 in Betz cells are incompletely understood; but, it is conceivable that the further spread of the pathology to interconnected neurons takes place by means of the phylogenetically 'new' or recent monosynaptic contacts [9,29,32,[37][38][39][40][41]. Whether the same holds true not only for corticobulbar and corticospinal projections but also for corticorubral and corticostriatal connectivities is currently an open question.…”
Section: The Pathology In Cortical Betz Cells Differs From That In Bumentioning
confidence: 99%
“…9 Similarly, recent work has also observed that TDP-43 aggregates from ALS brain and spinal cord can seed cellular TDP-43 aggregation after protein transfection, and that aggregates can move cell to cell in a co-culture system using HEK293 cells. 10 An additional study presented evidence to suggest that TDP-43 can transfer between HEK293 cells and primary cortical mouse neurons and interact with endogenous TDP-43 in recipient cells. 11 More recently, it was observed that TDP-43 fibrils formed from short C-terminal derived peptides triggered the seeddependent aggregation of wild type TDP-43 (TDP-43 WT ) or TDP-43 lacking a nuclear localization signal in SH-SY5Y cells resulting in different peptides sequences of TDP-43 producing fibrils with distinct biochemical properties reminiscent of prion strains.…”
Section: Introductionmentioning
confidence: 99%